Study on the Interactions Between Caffeoylquinic Acids With Bovine Serum Albumin: Spectroscopy, Antioxidant Activity, LC-MSn, and Molecular Docking Approach - Jiao, Qishu; Zhang, Wei; Jiang, Yanyan; Jiang, Lijuan; Chen, Xiangyang; Liu, Bin (Frontiers in Chemistry, 2019)
Clarified the binding mechanism of drugs with plasma proteins could provide fresh insights into the drug development. Caffeoylquinic acids (CQAs) are a kind of phenolic acid compounds which has extensive biological effects. This study investigated the binding mechanism of three CQAs, including chlorogenic acid, neochlorogenic acid and cryptochlorogenic acid, with bovine serum albumin (BSA) by using multi-spectroscopic techniques, including fluorescence, UV-Vis, Fourier transform infrared (FT-IR) and circular dichroism (CD) spectroscopy, LC-MSn, molecular docking and antioxidant activity assessment. In addition, the influences of PBS buffer, Tris-HCl buffer and water as solvents on the characteristics of CQAs and BSA interaction were also investigated. The results showed that intrinsic fluorescence of BSA was quenched by CQAs and the interaction was static quenching with the formation of a non-fluorescent complex. The binding of CQAs and BSA was spontaneous, and Van der Waals forces and hydrogen-bond interaction occupied crucial roles in the binding. All the three CQAs could bind to Site I in Domain IIA. The weakest interaction between neochlorogenic acid and BSA may due to its larger polarity. The results also indicated that the binding affinity of CQAs had a descending order of Tris-HCl > H2O > PBS, which could be attributed to hydrolase activity in different solvents. This study firstly clarified the binding mechanism of CQAs with BSA and changes of the binding in different solvents, and provided fresh insights into this drug transportation and metabolism.